How does technological diversity in supplier network drive buyer innovation? Relational process and contingencies - Gao, Gerald Yong; Xie, En; Zhou, Kevin Zheng (Journal of Operations Management, 2015)
AbstractExternal networks provide important knowledge sources of innovation for firms. Drawing on social network theory, this study examines how technological diversity in supplier network influences a focal buyer firm's innovation. The results from a survey of 202 Chinese manufacturing firms and their supplier networks reveal that novel information sharing partially mediates the effect of technological diversity in supplier network on buyer firms’ new product creativity. The positive effect of technological diversity is enhanced by buyer–supplier relational strength but inhibited by supplier network density; competitive intensity positively moderates this effect, and technological turbulence negatively moderates it. These findings provide novel insights into how buyer firms can use their supplier networks to enhance product innovation.